TRANSACTIONAL LEADERSHIP ON EMPLOYEE PERFORMANCE: JOB SATISFACTION AS A MODERATING VARIABLES - Setiani, Setiani; Rizaldy, Azhar (Jurnal Ilmiah Manajemen & Bisnis, 2021)
The purpose of this study is to see how transactional leadership affects employee performance using work satisfaction as a moderating variable. The methodologies used in this investigation are quantitative. The participants in this study were 100 employees of the Malang Regency's Kepanjen tax office. The sampling technique used a probability sampling technique with an accidental sampling approach. The sample used is 80 employees. Collecting data using questionnaires and interviews. Partially Least-Square Structural Equation Modelling (PLS-SEM) was utilized to analyze the data in this study. Transactional leadership has a good and significant effect on employee performance, according to the findings. Job satisfaction can moderate the impact of transactional leadership on employee performance at the Malang district tax service.